Error of large-eddy simulation in the wall pressure fluctuation of a turbulent channel flow. Issue 4 (May 2021) - Li, Rong; Yang, Bowen; Yang, Zixuan; Wang, Shizao; He, Guowei
Highlights: Error sources of LES in wall pressure fluctuation are analyzed. Error induced by filter operation only influences wall pressure fluctuation around the cut‐off wavenumber. Error in the velocity field is mainly responsible for the error in wall pressure fluctuation. The present study provides basis for future LES studies of wall pressure fluctuations. Abstract: We analyze the error of large-eddy simulation (LES) in wall pressure fluctuation of a turbulent channel flow. To separate different sources of the error, we conduct both direct numerical simulations (DNS) and LES, and apply an explicit filter on DNS data to obtain filtered DNS (FDNS) data. The error of LES is consequently decomposed into two parts: The first part is the error of FDNS with respect to DNS, which quantifies the influence of the filter operation. The second part is the difference between LES and FDNS induced by the error of LES in velocity field. By comparing the root-mean-square value and the wavenumber-frequency spectrum of the wall pressure fluctuation, it is found that the inaccuracy of the velocity fluctuations is the dominant source that induces the error of LES in the wall pressure fluctuation. The present study provides a basis on future LES studies of the wall pressure fluctuation.